How Not to Play an Indian Mythic: Raji: A Modern Fantasy - Chaudhury, Arkabrata; Chaudhuri, Arunoday (CyberOrient, 2023)
The current paper analyses the video game Raji: An Ancient Epic (Nodding Head Games 2020) to determine the accuracy of its representation of historical Indian experiences, in the domains of architecture, aesthetics, spatiality, technology, and so on. The ludic elements of the game, including weapon or enemy design and their compatibility with reflecting an Indian ethos in video game mechanisms have also been discussed. The treatment of Indian mythology is extensively explored, with an eye to locating its space in Indian mythic tradition. Through an analysis of narrative storytelling in the game, aspects such as the foregrounding of a female protagonist and the apparent progressive feminist attitude of the game have been scrutinised. The sociocultural depiction of India and its implications and contexts relating to contemporary understanding of the space of the subcontinent has also been taken into consideration. A careful study of the game within the contemporary post‐colonial discourse constitutes a part of the article. We also undertake a comparative study with another Indian mythic video game, Unrest (Pyrodactyl 2014), to better understand the issues surrounding the treatment of mythic and historical elements. The article both contemplates the missed opportunities and future potentials, for example, in terms of more nuanced and accurate representation and the balance between ludic execution and representational possibilities, as experienced in the ludo‐narrative experience offered by the game.